Model pembelajaran hypnoteaching dalam pembelajaran bahasa Jawa - Susilowati, Aditiyas Nurriyah Sriningsih; Sukoyo, Joko (Universitas Mulawarman, 2025)
This study employed a quantitative approach with a post-test only control group experimental design to investigate the impact of the hypnoteaching model on Javanese language learning in high school. The research subjects were 288 students, with two classes, X-5 as the experimental class and X-7 as the control class, randomly selected. According to the study, students who received instruction using the hypnoteaching approach showed increased motivation and learning outcomes. Observation data indicated that the experimental class's post-test score was 71.67, significantly higher than the control class's score of 50.56. With a sig. (2-tailed) value of 0.000, far below 0.05, the T-test revealed a significant difference between the two groups. Due to monotonous teaching strategies such as lectures, students in the traditional group were less motivated and more likely to become disengaged. Conversely, using hypnoteaching increased student motivation and made the class more enjoyable. This study shows that, compared to traditional teaching approaches, the hypnoteaching model is more effective in enhancing student motivation and learning outcomes.